History and Problems of Research on The Origins of the Sanskrit Drama - Jaskūnas, Valdas (Acta Orientalia Vilnensia, 2000)
There are many books and articles dealing with a problem of the origin of Sanskrit drama though the majority of them restrict themselves on the exposition of the theories and hypothesis without pointing out to the circumstances that propelled them. The main focus of this article, thus, is to reveal the impacts that enabled the spread of ideas concerning the origins of the Sanskrit drama in Western indology as well as the dynamics of their occurrence which lend the insights into the methodologies applied to the studies of the problem. From the discussion about the origin of drama since the late 19 c. it is evident that even now no one can assert with certainty about the early forms of drama. The tendencies of recent research show the main methodological principle which is that every new problem that occur in the field is closely connected with the data of the studies of cultural, ritual and intellectual traditions even then we are directly concerned with the texts such as the Nāyaśāstraa.